At home in two countries : the past and future of dual citizenship - Spiro, Peter J. (Citizenship and migration in the Americas., 2016)
At Home in Two Countries charts the history of dual citizenship from strong disfavor to general acceptance. The status has touched many; there are few Americans who do not have someone in their past or present who has held the status, if only unknowingly. The history reflects on the course of the state as an institution at the level of the individual. The state was once a jealous institution, justifiably demanding an exclusive relationship with its members. Today, the state lacks both the capacity and the incentive to suppress the status as citizenship becomes more like other forms of membership. Dual citizenship allows many to formalize sentimental attachments. For others, it's a new way to game the international system. This book explains why dual citizenship was once so reviled, why it is a fact of life after globalization, and why it should be embraced today.